2022
DOI: 10.1039/d1ta10132c
|View full text |Cite
|
Sign up to set email alerts
|

Experimental synthesis, functionalized modifications and potential applications of monoelemental zero-dimensional boron nanomaterials

Abstract: The past decade has witnessed a rapid growth in scientific studies on zero-dimensional (0D) boron nanomaterials, mainly involving boron nanoparticles, boron quantum dots, boron nanodots, boron nanoclusters and functionalized 0D...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 180 publications
0
18
0
Order By: Relevance
“…Boron has shown high promise as a fuel additive for propulsion and energetic applications due to its high gravimetric (58 kJ/g) and volumetric (140 kJ/mL) enthalpies of oxidation. Its ignition performance, however, is hindered by the presence of a native oxide on the surface, which melts at relatively low temperatures (450 °C at atmospheric pressure). The melting of the oxide shell before the solid core clogs the pores leads to particle agglomeration and acts as a diffusion barrier to the incoming oxidizer, thus delaying the boron (B) oxidation. , Attempts to overcome these limitations include surface functionalization of B by organic compounds, reduction of the oxide, followed by surface passivation using nonthermal plasma processing, and coating with metals to form composites and metal borides by ball milling and high-temperature sintering methods. Functionalization with organic compounds results in the reduction of the amount of energy released per unit mass due to the presence of less energetic materials on the B surface. Nonthermal plasma processing has been shown to be successful in enhancing the energetic performance over untreated boron but requires low-pressure equipment that is harder to scale-up.…”
Section: Introductionmentioning
confidence: 99%
“…Boron has shown high promise as a fuel additive for propulsion and energetic applications due to its high gravimetric (58 kJ/g) and volumetric (140 kJ/mL) enthalpies of oxidation. Its ignition performance, however, is hindered by the presence of a native oxide on the surface, which melts at relatively low temperatures (450 °C at atmospheric pressure). The melting of the oxide shell before the solid core clogs the pores leads to particle agglomeration and acts as a diffusion barrier to the incoming oxidizer, thus delaying the boron (B) oxidation. , Attempts to overcome these limitations include surface functionalization of B by organic compounds, reduction of the oxide, followed by surface passivation using nonthermal plasma processing, and coating with metals to form composites and metal borides by ball milling and high-temperature sintering methods. Functionalization with organic compounds results in the reduction of the amount of energy released per unit mass due to the presence of less energetic materials on the B surface. Nonthermal plasma processing has been shown to be successful in enhancing the energetic performance over untreated boron but requires low-pressure equipment that is harder to scale-up.…”
Section: Introductionmentioning
confidence: 99%
“…After experimental realization of 0D boron, scientists expanded borophene studies from the 2D planar scale to the 0D particle scale, such as boron nanoclusters, nanodots, nanoparticles (BNPs), and quantum dots (BQDs). As an emerging 0D monoelemental nanomaterial, 0D boron has been theoretically predicted to exhibit excellent properties and functions. In recent years, 0D boron has been realized experimentally and functionally modified toward promising applications, including biomedicine, imaging, sensing, adsorption, and optoelectronics. …”
Section: Introductionmentioning
confidence: 99%
“…23−32 In one of the latest reviews, we summarized major synthesis details, properties, and potential applications of various monoelemental 0D boron nanomaterials. 32 Particularly, previous experimental studies rarely involved fluorescence (FL) of 0D boron for sensing and imaging, except for BNPs for O 2 sensing and cell imaging. 33 Previous studies reported the FL emission behaviors of BQDs, 22 crystalline borophene quantum dots, 20 and boron nanospheres as derivatives of BQDs 34 but did not further involve FL sensing and imaging.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In general, 0D materials exhibit stronger edge effects and unique catalytic properties due to the extraordinary size. The rich unsaturated edge sites and improved charge transfer dynamics make 0D materials promising for PIHC devices 41‐45 . However, there are few works on 0D PIHC electrode materials, which are waiting to be explored by scholars.…”
Section: Introductionmentioning
confidence: 99%
“…The rich unsaturated edge sites and improved charge transfer dynamics make 0D materials promising for PIHC devices. [41][42][43][44][45] However, there are few works on 0D PIHC electrode materials, which are waiting to be explored by scholars.…”
Section: Introductionmentioning
confidence: 99%